Examining the effects of parental migration on youth mental health and substance use: a qualitative study in rural Yucatán, México - Zúñiga, María Luisa; Mulholland, Kayla; Lewin-Fischer, Pedro; Martinez San Román, Isela; Toledo, Lidiane; Urada, Lianne (Frontiers in Psychiatry, 2024)
Parental migration is common in Mexico and Latin America, where individuals pursue work to improve their family's economic opportunities and children remain home in their community under the care of the remaining parent or extended family. A research gap remains about the impact of parental migration on mental health and substance use in children who remain at home. The current study explored risk and resilience factors relating to mental health and substance use among Mexican youth remaining at home when one or more parents migrate. Methods: This qualitative study applied attachment theory and thematic analysis to analyze 26 in-depth interviews with youth (17-21 years old), parents, and a focus group with high-school teachers in a town with history of migration both domestically and internationally (Yucatan, México). Results: Respondents across groups perceived that parental migration was related to 1) less parental/caregiver oversight and support due to family demands on the remaining parent and 2) the deterioration of youth mental health. Lack of youth oversight and the poor mental health of youth were perceived as drivers of youth seeking out and consuming alcohol and substances. In terms of parental remittances, youth reported observing among their peers increased access to material goods such as clothing and technology (e.g., smartphones) and increased access to alcohol. Resilience factors included parental awareness of the role of good communication with youth and teachers and youth access to and utilization of self-care resources such as mutual aid meetings for substance use recovery.Poor mental health and substance use among youth and parents were perceived to be related to parental absence, stressors on the remaining parent or family, and undermined healthy parent-child attachment. Youth themselves are a source of insight for recommendations on interventions to reduce youth isolation and substance use risk. We recommend the intentional engagement of youth in developing intervention research and tailoring evidence-based interventions to mitigate parental absence's impact and promote parent-child attachment for youth and families remaining at home.